Analisis Faktor - Faktor Yang Mempengaruhi Motif Belanja Secara Online Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Ardi, Chrisna Yosefa Setya; , Muzakar Isa, S.E., M. Si (2016)
This study aims to identify factors - factors that influence online shopping motif. And which factors most influence on the motive of shopping online. The analysis tool used is multiple linear regression, by retrieving data using questionnaires the respondents Faculty of Economics and Business, University of Muhammadiyah Surakarta class of 2011 to 2015. This study refers to the positive approach, the approach which began the study with a hypothesis and then followed by hypothesis testing , Variable pricing and the confidence effect but not significant to the motive of shopping online. While psychological factors and knowledge of Internet technologies significantly influence online shopping motives. The independent variables consisting of price, trust, psychology, and knowledge of internet technologies together (simultaneously) motid variables significantly influence online shopping. Where obtained F count equal to 6.537 with a significance level of 0.000. R square value in this study, which amounted to 0.216 means that 21.6% variable online shopping motives can be explained by the variable price, trust, psychology, and knowledge of internet technology, while the remaining 78.4% is explained by other factors. Thus online businesses should be able to affect the psychological, and provide easy access to internet and info on the internet clearly for consumers in order to dominate the market.